Sero-prevalence of brucellosis, Q-fever and Rift Valley fever in humans and livestock in Somali Region, Ethiopia. - Mohammed Ibrahim; Esther Schelling; Jakob Zinsstag; Jan Hattendorf; Emawayish Andargie; Rea Tschopp (Public Library of Science (PLoS), 2021)
Information on zoonotic diseases in humans and livestock are limited in pastoral/agro-pastoral communities in Ethiopia. A multi-stage cross sectional cluster design study was implemented with the aim to establish the seroprevalence of zoonotic diseases including brucellosis, Q-fever and Rift Valley fever (RVF) in humans and livestock in Adadle Woreda of the Somali Region, Ethiopia. Blood samples were collected from humans and livestock and tested by relevant serological tests. For brucellosis, Rose Bengal test (RBT) and indirect ELISA was used for screening and confirmatory diagnosis respectively. Indirect and competitive ELISA were also used for Q-fever and RVF respectively. The individual seropositivity of Q-fever in livestock was 9.6% (95% CI 5.9-15.1) in cattle, 55.7% (95% CI 46.0-65.0) in camels, 48.8% (95% CI 42.5-55.0) in goats, and 28.9% (95% CI 25.0-33.2) in sheep. In humans, seropositivity of Q-fever was 27.0% (95% CI 20.4-34.0), with prevalence in males of 28.9% vs 24.2% in females (OR = 1.3; 95% CI 0.6-2.5). Camel seropositivity of Q-fever was significantly associated with age (OR = 8.1; 95% CI 2.8-23.7). The individual apparent seroprevalence of RVF was 13.2% (95% CI 8.7-18.8) in humans, 17.9% (95% CI 11.0-27.8) in cattle, 42.6% (95% CI 34.8-50.7) in camels, 6.3% (95% CI 3.3-11.6) in goats and 7.4% (95% CI 4.7-11.5) in sheep. Camels had the highest seropositivity of both Q-fever and RVF. Only a weak correlation was observed between human and livestock seropositivity for both Q-fever and RVF. Only cattle and camels were seropositive for brucellosis by iELISA. The individual seroprevalence of brucellosis was 2.8(0.9-6.4) in humans, 1.5% (95% CI 0.2-5.2) in cattle and 0.6% (95% CI 0.0-3.2) in camels. This study showed the importance of zoonoses in Somali Region and is the first published study to describe RVF exposure in humans and livestock in the country. Even though human exposure to RVF virus was reported, public health sector of Somali Region has not given attention to such zoonoses. Collaboration between public and animal health sectors for further investigation on these zoonoses using the One Health concept is indispensable.